Gelfoam for Closure of Large Percutaneous Transhepatic and Transsplenic Puncture Tracts in Pediatric Patients - Uller, W.; Müller-Wille, R.; Grothues, D.; Schelling, J.; Zausig, N.; Loss, M.; Stroszczynski, C.; Wohlgemuth, W. A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: Evaluation of the efficacy and safety of Gelfoam for the closure of transhepatic or transsplenic parenchymal puncture tracts with large-bore sheaths in pediatric patients.Materials and Methods: Between January 2012 and May 2013, 8 percutaneous transhepatic accesses and 3 percutaneous transsplenic accesses were closed using percutaneous Gelfoam in pediatric patients. The primary study endpoints to determine treatment efficacy and safety were patient survival, technical success defined as successful closure of the puncture tract without signs of bleeding, and complication rates. The secondary study endpoints were the occurrence of local and systemic inflammation.Results: Overall survival was 100 % with a median follow-up of 256 days. The procedure was technically successful in 10 of 11 procedures. One patient suffered from bleeding, which was successfully managed by a single blood transfusion. No re-bleeding was detected during follow-up and no surgical interventions were necessary. No signs of local or systemic infections related to the Gelfoam application occurred.Conclusion: Percutaneous Gelfoam application is an effective and safe technique for the closure of transhepatic or transsplenic accesses in pediatric patients.Key points: Interventional closure of large transhepatic and transsplenic parenchymal accesses in children after interventional treatment is recommended to avoid bleeding. Gelfoam application does not cause artifacts in magnetic resonance imaging and does not increase the risk of local or systemic inflammation in comparison to permanent embolic agents. Thus, especially children under immunosuppressive therapy can benefit from the application of Gelfoam.Citation Format:• Uller W, Müller-Wille R, Grothues D et al. Gelfoam for Closure of Large Percutaneous Transhepatic and Transsplenic Puncture Tracts in Pediatric Patients. Fortschr Röntgenstr 2014; 186: 693 – 697
Keywords: abdomen; embolization; transplantation; needle tract; intrahepatic; intrasplenic